Development Of A National-Style Women's Clothing Collection Mudslide. - Baxtiyor Xamraxo`jayev Yaxyoxo’novich (Genius Journals, 2024)
Even with a time when quality, convenient, and hygienically harmless appearance in the direction of "women's national clothing" for manufacturing companies is perfect, breathing is bringing innovation into the rapidly developing fashion world.
Keywords: Dress; Collection; Embroidery